TRADITIONAL APPROCHES TO TREATING ERECTILE DYSFUNCTION IN AFRICA (Nigerian Journal of Physiological Sciences, 2025)
Summary: Erectile dysfunction (ED) is an increasingly prevalent global health issue. Although FDA-approved   medications like sildenafil are available, their use is often accompanied by undesirable side effects. Consequently, there is growing interest in traditional medicine as an alternative treatment option. This review provides a detailed mechanistic analysis of key African medicinal plants utilized for managing erectile dysfunction. Relevant literature was obtained from authoritative scientific databases, including PubMed, Scopus, Web of Science, and Google Scholar. Search terms such as "erectile dysfunction," "African medicinal plants," "traditional medicine," and "mechanisms of action" were used to identify pertinent studies. A systematic review was conducted to evaluate research on African medicinal plants with reported efficacy in ED treatment. Studies were selected based on scientific rigor, pharmacological investigations, and mechanistic insights into their bioactive compounds and therapeutic pathways. Several African medicinal plants have demonstrated potential in treating ED through mechanisms such as boosting nitric oxide synthesis, modulating enzymatic pathways (e.g., phosphodiesterase-5 inhibition), and enhancing blood circulation. While existing studies highlight their effectiveness, there is still limited understanding of their precise molecular mechanisms and possible adverse effects. African medicinal plants offer a promising alternative for ED management. However, further research, including mechanistic studies and clinical trials, is essential to establish their safety, efficacy, and pharmacokinetics. This review emphasizes the importance of integrating traditional medicine into ED treatment strategies.Keywords: Erectile dysfunction, Medcinal plants, Herbal remedies, Traditional medicine.